Correlation between annual change in health status and computer tomography derived lung density in subjects with α1-antitrypsin deficiency. Issue 12 (26th November 2003) - Stolk, J; Ng, W H; Bakker, M E; Reiber, J H C; Rabe, K F; Putter, H; Stoel, B C
Abstract : Background: There is increasing recognition that questionnaires of health status and lung density measurements are more sensitive tools for assessing progression of emphysema than forced expiratory volume in 1 second (FEV1 ) and transfer coefficient (Kco ). A study was undertaken to investigate prospectively the correlation between annual change in health status and computer tomography (CT) derived lung density in subjects with α1 -antitrypsin deficiency. Methods: Twenty two patients of mean (SD) age 40.7 (9.2) years with ZZ type α1 -antitrypsin deficiency were investigated at baseline and 30 months later by FEV1 and Kco, St George Respiratory Questionnaire (SGRQ), and by a spiral CT scan of the chest. CT data of chest images were analysed using software designed for automated lung contour detection and lung density measurements. The density data were corrected for changes in inspiration levels. Results: Changes in lung density, expressed as 15th percentile point or relative area below –950 HU, correlated well with changes in health status (SGRQ total score): R = −0.56, p = 0.007 or R = 0.6, p = 0.003. Neither changes in health status nor changes in lung density correlated significantly with changes in FEV1 or changes in Kco . Conclusions: The SGRQ total score (which is a global measure in COPD) and lung density (a specific measure of emphysema) are sensitive to deterioration in patients with α1 -antitrypsin deficiency. This finding may facilitate future studies with new drugs specific for emphysema, a frequently occurring component of COPD.